SA Heart: Beating strong for South Africa’s cardiovascular health - Klug, Eric (SA Heart Journal, 2024)
The South African Heart Association (SA Heart®) stands as a vital pillar in our nation’s healthcare landscape. Our not-for-profit organisation, driven by a dedicated team and a resolute mission, serves as the powerful voice of cardiovascular care in South Africa. SA Heart®’s commitment extends far beyond advocacy – it fosters collaboration, propels research, and strives to ensure exceptional care for all South Africans, from the tiniest hearts to the most seasoned.